Setting Ambitious yet Achievable Targets Using Probabilistic Projections: Meeting Demand for Family Planning. Issue 3 (18th May 2017) - Kantorová, Vladimíra; New, Jin Rou; Biddlecom, Ann; Alkema, Leontine
Abstract: In 2015, governments adopted 17 internationally agreed goals to ensure progress and well‐being in the economic, social, and environmental dimensions of sustainable development. These new goals present a challenge for countries to set empirical targets that are ambitious yet achievable and that can account for different starting points and rates of progress. We used probabilistic projections of family planning indicators, based on a global data set and Bayesian hierarchical modeling, to generate illustrative targets at the country level. Targets were defined as the percentage of demand for family planning satisfied with modern contraceptive methods where a country has at least a 10 percent chance of reaching the target by 2030. National targets for 2030 ranged from below 50 percent of demand satisfied with modern contraceptives (for three countries in Africa) to above 90 percent (for 41 countries from all major areas of the world). The probabilistic approach also identified countries for which a global fixed target value of 75 percent demand satisfied was either unambitious or has little chance of achievement. We present the web‐based Family Planning Estimation Tool (FPET) enabling national decision makers to compute and assess targets for meeting family planning demand.